Development of E-banking channels and market share in developing countries - Ali Nazaritehrani; Behzad Mashali (Financial Innovation, 2020)
There is fierce global competition within the banking industry. Therefore, banks endeavor to grow and strive to increase their market share. We analyzed the effect of developing innovative channels of presenting bank services on banks' market share. The statistical population of this research was Shahr bank's central headquarter and its branches in Tehran, Iran. We developed questionnaires for gathering the data. The validity and reliability of the scales were tested by EFA, CFA, experts' opinion, and Cronbach's alpha. We used linear regression to assess the impact of innovative channels, including internet banking, automatic teller machines (ATMs), mobile banking, telephone banking (TB), and point of sales (POS) on banks' market share. The results indicated that some of these channels, including internet banking, POS, and TB, positively affect a bank's market share. The effect of two other platforms, including mobile banking and ATM development, on banks' market share was rejected. The findings of this study expand our understanding of how bank managers can improve their market share by developing innovative e-banking channels.
Keywords: 650; E-banking channels; New banking services; Bank market share; Innovative services; Bank marketing